Modelos de gestão de hospitais estaduais do SUS sob administração direta - Pereira, Samantha Souza da Costa (2016)
Hospitals are very complex structures and represent the most traditional way of organization in the health sector. Managing these organizations is a very challenging and equally difficult task. The Unified Health System (SUS) is endowed with an agreed hospital network and another own network, which may be administered directly by the State (Direct Administration) or by third parties (Indirect Administration). Direct Administration, here discussed, involves different management models. In this study, three paradigms of public administration, present in SUS hospitals are discussed: Patrimonialist, Bureaucratic and New Public Management. Composing intrinsically the management apparatus, there is the decision-making process, which constitutes an extremely relevant instrument in the administrative area. Thus, this research has as a general objective: to analyze the model of hospital management of the State Health Secretariat of Bahia (SESAB), under direct administration. To do so, a qualitative investigation was carried out through a case study, conducted in three large state hospitals under Direct Administration. Senior managers from the hospitals participated in this study, as well as a director of SESAB, who were submitted to the semi-structured interview. Other primary and secondary data sources were used, consisting of freely accessible documents. The data were analyzed in light of the Content Analysis, observing all the ethical principles contained in Resolution 466/12. As results, it was verified that the sociodemographic profile of the managers follows an expected pattern: majority of white men, with average age of 48 years, medical doctors, with specialization in hospital administration and having past experience. The perception of these managers about their management units pointed to serious demand problems. The management model characterized by the managers aggregates characteristics of the three management paradigms, with predominance of the Bureaucratic Model. When mentioning that the management model present in their action unit is “Participative”, managers approached the ideology advocated by the SUS, however, the organizational design of two of the hospitals studied indicates the existence of a still rigid structure. The decision-making process still followed a centralized practice. Thus, it is assumed that the adoption of a collegiate management model would be an alternative to democratize it, as it also is with the establishment of participatory decision-making processes. This study revealed that there is still a gap in the study of the management model present in hospitals administered by the State. Therefore, it is suggested that further studies should be carried out in this regard, as their results may lead to improvements in state administrative structures and contribute to the State’s ability to take over the management of the public machine.